Integrated Marketing Communication Strategy of Proposed Homecare Cleaning Product through New Product Development Process: A Case Study of PT. Siklus Refil Indonesia - Syarifah Khoiriyah; Dalimunthe, Gallang Perdhana (Management Analysis Journal, 2025)
The study aims to discover a new homecare cleaner product and its marketing strategy using New Product Development (NPD) and Integrated Marketing Communication (IMC) theory. PT. Siklus Refil Indonesia, the eco-friendly retail homecare cleaning company, faces a fall in revenue due to limited product development and inefficient marketing strategy. This study uses mixed methods involving home care cleaner users. The quantitative data is from the questionnaire, and the qualitative data is from nethnography, interviews, and the VRIO and PESTLE framework. The new product is developed based on the findings on netnography, and interviews strengthened with VRIO and PESTLE framework. The marketing strategy is defined based on IMC principles and insights from interviews and questionnaires. The findings are the new product to be developed is a multipurpose cleaner. The marketing strategy involves an integrated communication approach consisting of the eight channels tailor-made for the multipurpose cleaner, which are advertising, sales promotion, online and social media marketing, event and experience, mobile marketing, public relations and publicity, direct and database marketing, and personal selling.